2018
DOI: 10.1111/ecin.12703
|View full text |Cite
|
Sign up to set email alerts
|

Is More Competition Always Better? An Experimental Study of Extortionary Corruption

Abstract: Using a laboratory experiment, we assess whether increasing competition among public officials reduces extortionary corruption. We find that increasing the number of providers has no effect on bribe demands when citizens' search costs are high, but it increases corruption when search costs are low. The effect is absent in a parallel setting framed as a standard market, which we attribute to citizens using a nonsequential search strategy as opposed to sequential search in the corruption setting. We conclude tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 72 publications
(107 reference statements)
0
7
0
Order By: Relevance
“…Among the latter, we found a strong prevalence of initiatives aimed at increasing transparency of information and at reducing the asymmetry of information available for both suppliers and consumers of public services. Introducing competition in public service delivery is addressed by two studies and proves to be effective in reducing extortionary bribery, but only if the costs that citizens have to bear for searching alternative providers for the same service can be reduced (e.g., lowering transportation costs or improving information sharing mechanisms) (Ryvkin & Serra, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Among the latter, we found a strong prevalence of initiatives aimed at increasing transparency of information and at reducing the asymmetry of information available for both suppliers and consumers of public services. Introducing competition in public service delivery is addressed by two studies and proves to be effective in reducing extortionary bribery, but only if the costs that citizens have to bear for searching alternative providers for the same service can be reduced (e.g., lowering transportation costs or improving information sharing mechanisms) (Ryvkin & Serra, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As Basu, Basu and Cordella (2016) showed that asymmetric punishment (expected penalties) controls or contributes to reducing bribery rates in the country. Moreover, several studies found that asymmetric punishment successfully reduces bribery incidents (Abbink et al, 2014;Ryvkin & Serra, 2017;Verma & Sengupta, 2015).…”
Section: Arguments Of Asymmetric Measure For Bangladeshmentioning
confidence: 99%
“…Basu argues that bribe-takers will hesitate to take bribes after knowing this, which helps "sharp decline in the incidence of harassment bribe". Verma and Sengupta (2015) found that Basu proposal of asymmetric penalty significantly reduces bribery incidents under Basu proposal of an asymmetric penalty scheme and found that the inability of the bribe-takers to react against the bribe-giver correlates with the reduction in bribery incidents (Ryvkin & Serra, 2017). In an endogenous environment, implementing Basu proposal produced mixed results; one, the policy could reduce welfare and another, it would reduce harassment and non-harassment bribes (Oak, 2015).…”
mentioning
confidence: 99%
“…Such behavior becomes less frequent if the interaction is framed as bribery (Banerjee 2016). It becomes more frequent if officials compete with each other (Ryvkin and Serra 2015). It is substantially reduced if the private person is not punished (Abbink, Dasgupta et al 2014).…”
Section: D) Corruptionmentioning
confidence: 99%